Efektivitas Implementasi Intervensi Keperawatan dengan Inovasi “DEKADEE” dalam Mengontrol Gula Darah pada Pasien Diabetes Lansia di Masyarakat - Safaruddin; Rekawati, Etty; Sahar, Juniati (Journal of Pubnursing Sciences, 2024)
Introduction: Diabetes Mellitus (DM) is one of the leading non-communicable diseases (NCDs) in Indonesia, ranking as the sixth leading cause of death. The impact of DM on health has been increasingly detrimental over the years, necessitating serious mitigation efforts. As a response, an innovative nursing intervention known as "DEKADEE" (Diet, Foot Exercise, and Benson Relaxation) was developed. This study aims to evaluate the effect of the DEKADEE nursing intervention on reducing blood sugar levels in elderly diabetes patients. Methods: A community case study design with a pre-experimental approach was used to evaluate the effect of the DEKADEE intervention (Diet, Foot Exercise, Benson Relaxation) on the behavior and blood sugar levels of 44 elderly individuals with diabetes in Jatijajar, Depok. Pre- and post-intervention data were measured using the Easy Touch device and a behavior assessment instrument, analyzed with a paired T-test (p < 0.05). Results: Significant improvements were observed in elderly behavior, with knowledge increasing by 3.95 points, attitudes by 2.53 points, skills by 3.66 points, and a reduction in blood sugar levels by 61.045 mg/dL. A paired T-test on behavior variables and blood sugar levels showed significant results, with a p-value of 0.000 (p < 0.05). Conclusion: The DEKADEE Nursing Intervention significantly influenced behavior and had a profound impact on controlling random blood sugar levels in elderly individuals in Jatijajar Subdistrict, Depok City.